2016
DOI: 10.5271/sjweh.3589
|View full text |Cite
|
Sign up to set email alerts
|

Physical and cognitive capability in mid-adulthood as determinants of retirement and extended working life in a British cohort study

Abstract: In addition to the immediate benefits of having a healthy workforce, interventions which start in midlife or earlier to promote worker's physical and cognitive capability could have long-term consequences by enabling extended working lives and promoting a more positive experience of retirement. This is the first longitudinal study to consider performance-based and subjective reports of physical capability. Affiliation: MRC Unit for Lifelong Health and Ageing at UCL, 33Bedford Place, London WC1B 5JU, UK. m.staf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 29 publications
2
26
0
Order By: Relevance
“…When studying the effects of retirement on cognition, it is important to consider reverse causality. Declines in cognitive function may negatively affect the management of work tasks and thus could be a determinant of the decision to retire [ 31 , 32 ]. For example, chronic diseases, such as stroke, might affect both cognitive function and retirement decisions [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…When studying the effects of retirement on cognition, it is important to consider reverse causality. Declines in cognitive function may negatively affect the management of work tasks and thus could be a determinant of the decision to retire [ 31 , 32 ]. For example, chronic diseases, such as stroke, might affect both cognitive function and retirement decisions [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis showed that self-rated poor health was a risk factor for disability benefit (relative risk (RR) 3.61), unemployment (RR 1.44), and early retirement (RR 1.27) (3). Chronic diseases and limitations in daily activities also have been found to increase the likelihood of exit from paid employment (4,5).…”
mentioning
confidence: 99%
“…Yet even if all social classes left work at the same age, class differences in life expectancy means that lower classes will live fewer years after stopping work than professional classes. Some researchers have suggested that SPA should directly reflect life expectancy differences, 38 where retirement eligibility age is determined by the type of job. 39 Alternatively, the eligibility age requirement could be dropped, so that State Pension eligibility is solely determined by 14 accumulation of years of full-time equivalent work.…”
Section: Discussionmentioning
confidence: 99%
“…39 Alternatively, the eligibility age requirement could be dropped, so that State Pension eligibility is solely determined by 14 accumulation of years of full-time equivalent work. 38 The recent Independent Review of the State Pension argued for keeping a uniform SPA out of the principle of universality for the pension benefit, but to mitigate disadvantage through a means-tested one year early SPA for those who are unable to work through ill health or caring responsibilities. 1 We believe a two-year early SPA may be more appropriate for individuals who work in manual occupations, given that they leave work a year earlier than professional workers not in good health.…”
Section: Discussionmentioning
confidence: 99%